1998
DOI: 10.1063/1.122875
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of silicon exfoliation induced by hydrogen/helium co-implantation

Abstract: Infrared spectroscopy and secondary ion mass spectrometry are used to elucidate the mechanism by which co-implantation of He with H facilitates the shearing of crystalline Si. By studying different implant conditions, we can separate the relative contributions of damage, internal pressure generation, and chemical passivation to the enhanced exfoliation process. We find that the He acts physically as a source of internal pressure but also in an indirect chemical sense, leading to the reconversion of molecular H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…We now can combine these elements to first propose a coherent mechanism for the hydrogen induced exfoliation of germanium and then compare it with the mechanism developed elsewhere for silicon. 7,23 The first important observation is that after implantation hydrogen is located mainly in defect structures such as hydrogenated vacancies with different degrees of hydrogenation. The dominant features in the spectrum taken with s-polarization are at 1979, 2008, and 2050 cm −1 , which are respectively consistent with interstitial defects and monoand multi-hydrogenated vacancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We now can combine these elements to first propose a coherent mechanism for the hydrogen induced exfoliation of germanium and then compare it with the mechanism developed elsewhere for silicon. 7,23 The first important observation is that after implantation hydrogen is located mainly in defect structures such as hydrogenated vacancies with different degrees of hydrogenation. The dominant features in the spectrum taken with s-polarization are at 1979, 2008, and 2050 cm −1 , which are respectively consistent with interstitial defects and monoand multi-hydrogenated vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This effect has been attributed to a synergy between the H-chemistry, that stabilizes the internal surface of the crack and breaks the Si-Si bond at the crack-tip, and the efficient crack pressurization provided by He. [8][9][10] Although the main physic concept of the coimplantation has been realized, it is a complex system for which the microstructure evolution strongly depends on experimental parameters, as the implantation order, energy range, and relative depth positions of H and He depth profiles.…”
Section: 2mentioning
confidence: 99%
“…In the delineation of a detailed model that explains the exfoliation process of silicon, Fourier transform infrared ͑FTIR͒ spectroscopy combined with other structural measurements such as transmission electron microscopy ͑TEM͒, atomic force microscopy ͑AFM͒, and forward-recoil scattering ͑FRS͒ has played a central role. [9][10][11] In these studies, it was shown that H-terminated vacancies form internal structures passivated with silicon mono-hydrides, where H 2 gas is segregated from the bulk semiconductor, providing the internal pressure necessary to form extended surfaces and cracks. The accumulation of H 2 into these cavities causes the internal pressure to rise to a level where the whole surface of silicon blisters.…”
Section: Introductionmentioning
confidence: 99%